A review of immunofluorescent patterns associated with antineutrophil cytoplasmic antibodies (ANCA) and their differentiation from other antibodies. Issue 8 (August 1998) - Savige, J A; Paspaliaris, B; Silvestrini, R; Davies, D; Nikoloutsopoulos, T; Sturgess, A; Neil, J; Pollock, W; Dunster, K; Hendle, M
Abstract : AIM: To describe the neutrophil fluorescent patterns produced by antineutrophil cytoplasmic antibodies (ANCA) with different antigen specificities, and by other auto- and alloantibodies. BACKGROUND: Most sera from patients with active generalised Wegener's granulomatosis result in diffusely granular cytoplasmic neutrophil fluorescence with internuclear accentuation (cANCA) and proteinase 3 (PR3) specificity. About 80% of the sera from patients with microscopic polyangiitis result in perinuclear neutrophil fluorescence with nuclear extension (pANCA) and myeloperoxidase (MPO) specificity, or a cANCA pattern with PR3 specificity. However, many different neutrophil fluorescence patterns are noted on testing for ANCA in routine immunodiagnostic laboratories. METHODS: Sera sent for ANCA testing, or containing a variety of auto- and alloantibodies, were studied. They were examined by indirect immunofluorescence according to the recommendations of the first international ANCA workshop, and for PR3 and MPO specificity in commercial and in-house enzyme linked immunosorbent assays (ELISA). RESULTS: Sera with typical cANCA accounted for only half of all neutrophil cytoplasmic fluorescence. Other sera had "flatter" fluorescence without internuclear accentuation, and the corresponding antigens included MPO and bactericidal/permeability increasing protein (BPI), but were usually unknown. Peripheral nuclear fluorescence without nuclear extension occurred typically when the antigens were BPI, lactoferrin, lysozyme, elastase, or cathepsin G. Most types of ANA were evident on ethanol fixed neutrophil nuclei. AntidsDNA, antiRo, and antilamin antibodies resembled pANCA. Antimicrobial and antiribosomal antibodies produced cytoplasmic fluorescence, and antiGolgi antibodies, a pANCA. Sera from patients with anti-smooth muscle antibodies were associated with cytoplasmic fluorescence. There was no neutrophil fluorescence with anti-skeletal muscle and anti-heart muscle antibodies, anti-liver/kidney microsomal, antithyroid microsomal, or antiadrenal antibodies. Alloantibodies such as antiNB1 typically resulted in cytoplasmic fluorescence of only a subpopulation of the neutrophils. CONCLUSIONS: The ability to distinguish between different neutrophil fluorescence patterns, and the patterns seen with other auto- and alloantibodies is helpful diagnostically. However, the demonstration of MPO or PR3 specificity by ELISA will indicate that the neutrophil fluorescence is probably clinically significant, and that the diagnosis is likely to be Wegener's granulomatosis or microscopic polyangiitis.